2013
DOI: 10.1002/ejlt.201100321
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oil phase concentration on droplet size distribution and stability of oil‐in‐water emulsions

Abstract: The objective of this study was to investigate the effect of oil phase concentration, at different emulsification conditions concerning homogenization time and emulsifier content, on droplet size distribution and stability of corn oil-in-water emulsions. Emulsions were prepared with 3, 5, 10, and 20% w/w triethanolamine oleate (calculated on oil amount), 0.53% w/w carboxymethylcellulose (calculated on water amount), and 5, 10, 20, 30, or 40% w/w oil, and homogenized 5, 10, 20, and 60 min. It was found that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…Our result is in agreement with the result reported in another research study, which found that increasing the oil phase percentage in the media may lead to globular enlargement as the specific surface area decreases and polydispersity of the emulsion increases [ 44 ]. The eugenol present in clove oil is responsible for the decrease of particle size to within the optimum nanosize [ 45 ].…”
Section: Resultssupporting
confidence: 93%
“…Our result is in agreement with the result reported in another research study, which found that increasing the oil phase percentage in the media may lead to globular enlargement as the specific surface area decreases and polydispersity of the emulsion increases [ 44 ]. The eugenol present in clove oil is responsible for the decrease of particle size to within the optimum nanosize [ 45 ].…”
Section: Resultssupporting
confidence: 93%
“…The employed range of oil/water (o/w) phase ratios, did not impact the hydrodynamic diameter (Figure 12). According to available bibliography, the high volume of continuous phase may decrease the collision rate of particles, and subsequent coalescence [55]. Nonetheless, the results did not confirm any aggregation.…”
Section: Discussionmentioning
confidence: 92%
“…The oil content can also significantly affect the droplet size of the composite. Higher oil phase content leads to a reduction in specific surface area and an increased droplet size, resulting in undesired swelling behavior [41]. …”
Section: Resultsmentioning
confidence: 99%